Multifunctional composite binder as well as preparation method and application thereof

By introducing double bonds and other groups into polyacrylic acid (PAA) binder, extending the branch length and introducing metal ions, a multifunctional composite binder is prepared, which solves the battery performance problems caused by hydrophilicity of PAA binder in lithium-ion batteries, and achieves better adhesion ability and battery performance.

CN119505755APending Publication Date: 2025-02-25ZHANGJIAGANG HUASHENG CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669793.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Due to the hydrophilicity of the carboxyl group in lithium-ion batteries, the residual moisture reacts with LiPF6 in the electrolyte, causing the organic solvent to decompose and affect the charging and discharge performance of the battery.

Method used

Methyl acrylate is used as the main structure of the polymer, and double bonds are first introduced, then hydroxy, cyano or ester groups are introduced to extend the branch length to form a polymer with multifunctional groups with network branching. Sodium ions, lithium ions or potassium ions are introduced during the polymerization process, and a multifunctional composite binder is obtained through solvent dissolution or emulsification.

Benefits of technology

The adhesion ability of this multifunctional composite adhesive is better than that of competitor PAA adhesive, has excellent high-temperature storage performance, and has better bonding effect than other adhesives, has a smaller amount of adhesive, and the battery performance is comparable to that of SBR.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505755A_ABST
    Figure CN119505755A_ABST
Patent Text Reader

Abstract

The invention relates to a multifunctional composite binder and a preparation method and application thereof.The preparation method comprises the steps that methyl acrylate serves as a polymer main body structure, double bonds are introduced firstly, then the double bonds, hydroxyl, cyano or ester groups are introduced, a polymer with a network branched chain and polyfunctional groups is formed, then sodium ions, lithium ions or potassium ions are introduced, and the multifunctional composite binder is obtained. The binder is obtained through solvent dissolution or emulsification, and the binder is applied to the battery. The composite binder disclosed by the invention has good solubility and is high in dissolution speed and solubility in a solvent, and the required solvent is safe, environment-friendly and non-toxic; meanwhile, the method is simple in technological process, short in route, easy to industrialize, free of three wastes, green, environment-friendly and pollution-free. The electrode prepared from the negative electrode slurry prepared from the composite binder has good conductivity and lithium ion conductivity, and the prepared lithium battery can realize long circulation and has a better capacity retention rate in the circulation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery preparation, and in particular to a multifunctional composite binder and a preparation method and application thereof. Background Art

[0002] In recent years, polyacrylic acid is often used as a binder for lithium-ion batteries. It has the following advantages: 1. It hardly swells in carbonate solvents in electrolytes, and the electrode sheet structure is stable during charge and discharge; 2. The carboxyl content in its structure is higher than that of CMC (carboxymethyl cellulose), and it can form stronger hydrogen bonds with active materials containing hydroxyl groups on the surface, promoting a more uniform coating on the electrode surface than CMC; 3. It can form a denser film in the electrode sheet, increasing the electrical contact between the active material and the current collector; 4. It has excellent tensile mechanical strength, which is conducive to mechanical processing. However, due to the presence of a large number of carboxyl groups in the structure of polyacrylic acid, although it has good viscosity, the carboxyl group is highly hydrophilic, and the residual water will react with LiPF6 in the electrolyte to decompose the organic solvent, affecting the charge and discharge performance of the battery. Therefore, it is very necessary to modify polyacrylic acid to improve its performance. Summary of the invention

[0003] Technical problem to be solved: In view of the shortcomings of the prior art, the present invention provides a multifunctional composite binder and a preparation method and application thereof. The multifunctional composite binder uses methyl acrylate as the main polymer structure, first introduces double bonds, and then introduces hydroxyl groups, cyano groups or ester groups, thereby extending the length of the side chains, forming strong hydrogen bonds with the hydroxyl groups on the surface of the active material, and being able to form an ideal conductive network with the conductive agent. The adhesion ability is superior to that of competing PAA binders.

[0004] Technical solution: A method for preparing a multifunctional composite adhesive, the steps are as follows: (1) Polymerization: dissolving an initiator in deionized water to prepare an initiator aqueous solution with a concentration of 6-12%, and uniformly mixing methyl acrylate and allyl acetate to obtain a mixed solution. The mixed solution is dripped into the initiator aqueous solution under an inert gas atmosphere at a temperature of 40-100° C. After the dripping is completed, a polymer containing a hydroxyl group, a cyano group or an ester group is continuously dripped under an inert gas atmosphere. The mixture is stirred at a stirring speed of 160-300 r / min for 2-4 hours and then filtered to obtain a multifunctional polymerization product having a network branch chain, wherein the molar ratio of methyl acrylate, allyl acetate, initiator and polymer is 1000:(1000-4000):(1-10):(50-250); (2) Alkalization: dissolve the alkalizer in deionized water to prepare an alkalizer aqueous solution with a concentration of 5%-15%, and add the alkalizer aqueous solution to the polymer product obtained in step (1) at a dropping speed of 100-800 mL / h. After the dropping is completed, add a solvent, raise the temperature to 40-100°C, wait for the polymer product to be completely dissolved, cool to 20°C, stir at a stirring speed of 200-300 r / min for 2 hours, and discharge the material to obtain a multifunctional composite adhesive, wherein the weight ratio of the polymer product, the alkalizer, and the solvent is 1: (4-30): (1-20).

[0005] The initiator in the above-mentioned step (1) is one or more of peroxides and azo compounds; the peroxide is dodecyl peroxide, sodium persulfate, potassium persulfate or benzoyl peroxide; the azo compound is azobisisobutyronitrile, dimethyl azobisisobutyrate or azobisisoheptylonitrile.

[0006] The polymer containing hydroxyl groups in the above-mentioned step (1) is one or more of polyvinyl alcohol, polypropylene alcohol and polyprene alcohol.

[0007] The cyano group-containing polymer in the above-mentioned step (1) is one or more of polyacrylonitrile and polymethacrylonitrile.

[0008] The polymer containing an ester group in the above-mentioned step (1) is one or more of polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polyvinyl acetate, and polypropylene acetate.

[0009] The alkalizing agent in the above-mentioned step (2) is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; the solvent is one or two of water, methanol, ethanol, acetone, ethyl acetate, acetonitrile, dichloromethane, dichloroethane, dimethyl carbonate, ethylene carbonate, vinylene carbonate, and tetrahydrofuran.

[0010] The multifunctional composite adhesive is prepared by the preparation method described above.

[0011] The multifunctional composite binder is used in preparing negative electrode slurry for lithium battery.

[0012] The negative electrode slurry described above contains the following components by mass: 95-97 parts of negative electrode active material; 0.5-2 parts of sulfur / polyacrylonitrile copolymer; 1-3 parts of the multifunctional composite binder; 0.1-1.5 parts of styrene-butadiene rubber; and 2-3 parts of ultrapure water.

[0013] The negative electrode active material mentioned above is one or two of graphite, silicon, lithium titanate, and titanium oxide.

[0014] The multifunctional composite binder of the present invention uses methyl acrylate as the main polymer structure, firstly introduces double bonds, and then introduces double bonds, hydroxyl groups, cyano groups or ester groups to form a multifunctional polymer with network branches, and then introduces sodium ions, lithium ions or potassium ions, and obtains a binder through solvent dissolution or emulsification, and the binder is applied to batteries.

[0015] Beneficial effects: The multifunctional composite adhesive provided by the present invention and its preparation method and application have the following beneficial effects: 1. The preparation method of the present invention first introduces double bonds during the polymerization process, and then introduces hydroxyl groups, cyano groups or ester groups to extend the length of the side chains, forming strong hydrogen bonds with the hydroxyl groups on the surface of the active material, and being able to form an ideal conductive network with the conductive agent. The adhesion ability is better than that of competing PAA binders.

[0016] 2. The composite binder of the present invention has excellent high-temperature storage performance, better bonding effect than other binders, less binder usage, and battery performance comparable to that of SBR.

[0017] 3. The composite binder of the present invention has good solubility, fast dissolution speed in solvent, high solubility, and the required solvent is safe, environmentally friendly and non-toxic; and the raw materials used in the present invention are widely available and low in cost; at the same time, the process of the present invention is simple, the route is short, easy to industrialize, free of three wastes, green, environmentally friendly and pollution-free.

[0018] 4. The electrode prepared by using the negative electrode slurry prepared by the composite binder of the present invention has good electrical conductivity and lithium ion conductivity. The prepared lithium battery can achieve long cycle and has better capacity retention rate during the cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the gel permeation chromatogram of the multifunctional composite adhesive prepared in Example 2.

[0020] Figure 2 This is a comparison chart of the adhesive impedance of the multifunctional composite adhesive prepared in Example 3.

[0021] Figure 3 The battery cycle performance graphs of the lithium batteries prepared in Examples 1-4 and Comparative Examples 1-2 are shown. DETAILED DESCRIPTION

[0022] This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0023] The sources of reagents used in all the following examples and comparative examples are as follows: Methyl acrylate was purchased from Sinopec Shanghai Petrochemical Co., Ltd.; Allyl acetate was purchased from Formosa Plastics Corporation; Polyacrylonitrile, polymethyl methacrylate, and polyvinyl acetate were purchased from Shenghong Refining and Chemical Co., Ltd.; Sodium persulfate, potassium persulfate, and benzoyl peroxide were purchased from Nouryon Chemicals Co., Ltd.; Polyvinyl alcohol was purchased from Anhui Wanwei Group; Sodium hydroxide and methanol were purchased from New World International Trading Company; Silicon-based negative electrode active materials, SBR (styrene-butadiene rubber), SP (sulfur / polyacrylonitrile copolymer), and electrolyte were purchased from MacLean; The battery electrodes and separators were purchased from Anage. Example 1

[0024] This embodiment provides a method for preparing a multifunctional composite adhesive, comprising the following steps: (1) Polymerization: 6.5 g of sodium persulfate was dissolved in 82.2 mL of deionized water in a reactor, and the temperature was raised to 65° C. to prepare a sodium persulfate aqueous solution. 237.5 g of methyl acrylate and 1104.6 g of allyl acetate were added to a dropping tank, and mixed evenly to obtain a mixed solution. The mixed solution was dropped into the sodium persulfate aqueous solution under an inert gas atmosphere at a temperature of 65° C. After the dropwise addition was completed, 57.4 g of polyacrylonitrile was added to the dropping tank, and the gas in the dropping tank and the reactor was replaced again to maintain an inert gas atmosphere. Polyacrylonitrile was continued to be dropped, and the mixture was stirred at a stirring speed of 160-300 r / min for 4 h, and then filtered to obtain a multifunctional polymerization product having a network branched chain; (2) Alkalization: 595.3 g of sodium hydroxide was dissolved in 5357 mL of deionized water to prepare a sodium hydroxide aqueous solution, and the sodium hydroxide aqueous solution was added to a dropping tank and added dropwise to the polymer product obtained in step (1) (i.e., in the reactor) at a dropping speed of 100-800 mL / h. After the dropping was completed, 1500 g of methanol was added, the temperature was raised to 40° C., and after the polymer product was completely dissolved, the temperature was lowered to 20° C. and stirred at a stirring speed of 200-300 r / min for 2 h. The multifunctional composite binder was obtained.

[0025] The multifunctional composite binder prepared in this embodiment is used to prepare a lithium battery, and the steps are as follows: The silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), the multifunctional composite binder, SBR (styrene-butadiene rubber), and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts by mass, 2 parts by mass, 0.5 parts by mass, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8 μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16 μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery. Example 2

[0026] This embodiment provides a method for preparing a multifunctional composite adhesive, comprising the following steps: (1) Polymerization: 7.4 g of potassium persulfate was dissolved in 106 mL of deionized water in a reactor, and the temperature was raised to 95° C. to prepare a potassium persulfate aqueous solution. 237.5 g of methyl acrylate and 1104.6 g of allyl acetate were added to a dropping tank, and mixed evenly to obtain a mixed solution. The mixed solution was dropped into the potassium persulfate aqueous solution under an inert gas atmosphere at a temperature of 65° C. After the dropwise addition was completed, 69 g of polymethyl methacrylate was added to the dropping tank, and the gas in the dropping tank and the reactor was replaced again to maintain an inert gas atmosphere. Polymethyl methacrylate was continued to be dropped, and the mixture was stirred at a stirring speed of 160-300 r / min for 4 h, and then filtered to obtain a multifunctional polymerization product having a network branched chain; (2) Alkalization: 595.3 g of sodium hydroxide was dissolved in 5357 mL of deionized water to prepare a sodium hydroxide aqueous solution, and the sodium hydroxide aqueous solution was added to a dropping tank and added dropwise to the polymer product obtained in step (1) (i.e., in the reactor) at a dropping speed of 100-800 mL / h. After the dropping was completed, 1600 g of methanol was added, the temperature was raised to 40° C., and after the polymer product was completely dissolved, the temperature was lowered to 20° C. and stirred at a stirring speed of 200-300 r / min for 2 h. The multifunctional composite binder was obtained.

[0027] The gel permeation chromatogram of the multifunctional composite binder is as follows: Figure 1 As shown, from Figure 1 It can be seen that the molecular weight of the multifunctional composite adhesive is 440,000.

[0028] The multifunctional composite binder prepared in this embodiment is used to prepare a lithium battery, and the steps are as follows: The silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), the multifunctional composite binder, SBR (styrene-butadiene rubber), and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts by mass, 2 parts by mass, 0.5 parts by mass, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8 μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16 μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery. Example 3

[0029] This embodiment provides a method for preparing a multifunctional composite adhesive, comprising the following steps: (1) Polymerization: 6.7 g of benzoyl peroxide was dissolved in 74.3 mL of deionized water in a reactor, and the temperature was raised to 55° C. to prepare an aqueous solution of benzoyl peroxide (here, 1.25 g of polyvinyl alcohol was added to the aqueous solution of benzoyl peroxide as a dispersant to better disperse methyl acrylate and allyl acetate in the liquid phase). 237.5 g of methyl acrylate and 1104.6 g of allyl acetate were added to a dropping tank, and mixed evenly to obtain a mixed solution. The mixed solution was dropped into the aqueous solution of benzoyl peroxide under an inert gas atmosphere at a temperature of 55-60° C. After the dropwise addition was completed, 50 g of polyvinyl acetate was added to the dropping tank, and the gas in the dropping tank and the reactor was replaced again to maintain an inert gas atmosphere. Polyvinyl acetate was continued to be dropped, and the mixture was stirred for 2 h at a stirring speed of 160-300 r / min, and then filtered to obtain a multifunctional polymerization product having a network branch chain; (2) Alkalization: 595.3 g of sodium hydroxide was dissolved in 5357 mL of deionized water to prepare a sodium hydroxide aqueous solution, and the sodium hydroxide aqueous solution was added to a dropping tank and added dropwise to the polymer product obtained in step (1) (i.e., in the reactor) at a dropping speed of 100-800 mL / h. After the dropping was completed, 2216 g of methanol was added, the temperature was raised to 40° C., and after the polymer product was completely dissolved, the temperature was lowered to 20° C. and stirred at a stirring speed of 200-300 r / min for 2 h. The multifunctional composite binder was obtained.

[0030] The multifunctional composite binder prepared in this embodiment is used to prepare a lithium battery, and the steps are as follows: The silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), the multifunctional composite binder, SBR (styrene-butadiene rubber), and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts by mass, 2 parts by mass, 0.5 parts by mass, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8 μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16 μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery.

[0031] The binder impedance comparison diagram of the multifunctional composite binder prepared in this embodiment is as follows: Figure 2 As shown. Figure 2 It can be seen that the semicircular arc in the figure is the capacitive reactance arc, and the slash behind it is W diffusion. The larger the radius of the arc, the greater the polarization resistance. It can be seen from the figure that the arc radius measured by the composite binder assembled battery is larger than the arc radius measured by the SBR assembled battery. The polarization resistance of the composite binder assembled battery is larger and its corrosion resistance is better. Example 4

[0032] This embodiment provides a method for preparing a multifunctional composite adhesive, comprising the following steps: (1) Polymerization: 6.5 g of sodium persulfate was dissolved in 82.2 mL of deionized water in a reactor, and the temperature was raised to 65° C. to prepare a sodium persulfate aqueous solution (here, 1.25 g of polyvinyl alcohol was added to the benzoyl peroxide aqueous solution as a dispersant to better disperse methyl acrylate and allyl acetate in the liquid phase). 237.5 g of methyl acrylate and 1104.6 g of allyl acetate were added to a dropping tank and mixed evenly to obtain a mixed solution. The mixed solution was dropped into the sodium persulfate aqueous solution under an inert gas atmosphere at a temperature of 65° C. After the dropwise addition was completed, 50 g of polyvinyl acetate was added to the dropping tank, and the gas in the dropping tank and the reactor was replaced again to maintain an inert gas atmosphere. Polyvinyl acetate was continued to be dropped, and the mixture was stirred for 2 h at a stirring speed of 160-300 r / min, and then filtered to obtain a multifunctional polymerization product with a network branch chain; (2) Alkalization: 595.3 g of sodium hydroxide was dissolved in 5357 mL of deionized water to prepare a sodium hydroxide aqueous solution, and the sodium hydroxide aqueous solution was added to a dropping tank and added dropwise to the polymer product obtained in step (1) (i.e., in the reactor) at a dropping speed of 100-800 mL / h. After the dropping was completed, 2566 g of methanol was added, the temperature was raised to 40° C., and after the polymer product was completely dissolved, the temperature was lowered to 20° C. and stirred at a stirring speed of 200-300 r / min for 2 h. The multifunctional composite binder was obtained.

[0033] The multifunctional composite binder prepared in this embodiment is used to prepare a lithium battery, and the steps are as follows: The silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), the multifunctional composite binder, SBR (styrene-butadiene rubber), and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts by mass, 2 parts by mass, 0.5 parts by mass, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8 μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16 μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery. Comparative Example 1

[0034] The comparative example prepared a lithium battery, and the steps were as follows: Silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), BASF SBR, and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts by mass, 2 parts by mass, 0.5 parts by mass, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8 μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16 μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery. Comparative Example 2

[0035] The comparative example prepared a lithium battery, and the steps were as follows: Silicon negative electrode active material, SP (sulfur / polyacrylonitrile copolymer), Ruiong SBR, and ultrapure water are mixed in a ratio of 97 parts by mass, 0.5 parts, 2 parts, 0.5 parts, and 3 parts by mass to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative current collector with a thickness of 4-8μm, and after drying, it is rolled, divided into strips, and made into sheets to obtain a negative electrode sheet; the above-mentioned negative electrode sheet, electrolyte, positive electrode sheet and 16μm separator are assembled into a soft-pack 2Ah battery cell to obtain a lithium battery.

[0036] The various properties of the lithium batteries prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the test results are shown in Table 1 below.

[0037] Table 1

[0038] The battery cycle performance spectra of the lithium batteries prepared in Examples 1-4 and Comparative Examples 1-2 are as follows: Figure 3 As shown in Table 1 and Figure 3 It can be seen that the lithium battery prepared in Example 4 has the best performance and the highest capacity retention rate; the performance of the lithium batteries prepared in Examples 1-3 is higher than that of Comparative Examples 1 and 2.

[0039] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a multifunctional composite adhesive, characterized in that Here are the steps: (1) Polymerization: dissolving an initiator in deionized water to prepare an initiator aqueous solution with a concentration of 6-12%, and uniformly mixing methyl acrylate and allyl acetate to obtain a mixed solution. The mixed solution is dripped into the initiator aqueous solution under an inert gas atmosphere at a temperature of 40-100° C. After the dripping is completed, a polymer containing a hydroxyl group, a cyano group or an ester group is continuously dripped under an inert gas atmosphere. The mixture is stirred at a stirring speed of 160-300 r / min for 2-4 hours and then filtered to obtain a multifunctional polymerization product having a network branch chain, wherein the molar ratio of methyl acrylate, allyl acetate, initiator and polymer is 1000:(1000-4000):(1-10):(50-250); (2) Alkalization: dissolve the alkalizer in deionized water to prepare an alkalizer aqueous solution with a concentration of 5%-15%, and add the alkalizer aqueous solution to the polymer product obtained in step (1) at a dropping speed of 100-800 mL / h. After the dropping is completed, add a solvent, raise the temperature to 40-100°C, wait for the polymer product to be completely dissolved, cool to 20°C, stir at a stirring speed of 200-300 r / min for 2h, and discharge the material to obtain a multifunctional composite adhesive, wherein the weight ratio of the polymer product, the alkalizer, and the solvent is 1: (4-30): (1-20).

2. The method for preparing a multifunctional composite adhesive according to claim 1, characterized in that: The initiator in step (1) is one or more of peroxides and azo compounds; the peroxide is dodecyl peroxide, sodium persulfate, potassium persulfate or benzoyl peroxide; the azo compound is azobisisobutyronitrile, dimethyl azobisisobutyrate or azobisisoheptylonitrile.

3. The method for preparing a multifunctional composite adhesive according to claim 1, characterized in that: The polymer containing hydroxyl groups in step (1) is one or more of polyvinyl alcohol, polypropylene alcohol and polyprene alcohol.

4. The method for preparing a multifunctional composite adhesive according to claim 1, characterized in that: The cyano group-containing polymer in step (1) is one or more of polyacrylonitrile and polymethacrylonitrile.

5. The method for preparing a multifunctional composite adhesive according to claim 1, characterized in that: The polymer containing an ester group in step (1) is one or more of polymethyl methacrylate, polymethyl acrylate, polyethyl acrylate, polypropyl acrylate, polyvinyl acetate, and polypropylene acetate.

6. The method for preparing a multifunctional composite adhesive according to claim 1, characterized in that: The alkalizing agent in step (2) is one or more of sodium hydroxide, potassium hydroxide, and lithium hydroxide; the solvent is one or two of water, methanol, ethanol, acetone, ethyl acetate, acetonitrile, dichloromethane, dichloroethane, dimethyl carbonate, ethylene carbonate, vinylene carbonate, and tetrahydrofuran.

7. A multifunctional composite adhesive prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the multifunctional composite binder as claimed in claim 7 in preparing negative electrode slurry for lithium batteries.

9. The use of the multifunctional composite binder according to claim 8 in preparing negative electrode slurry of a lithium battery, characterized in that The negative electrode slurry contains the following components in parts by mass: 95-97 parts of negative electrode active material; 0.5-2 parts of sulfur / polyacrylonitrile copolymer; 1-3 parts of the multifunctional composite binder; 0.1-1.5 parts of styrene-butadiene rubber; and 2-3 parts of ultrapure water.

10. Use of the multifunctional composite binder according to claim 9 in preparing negative electrode slurry for lithium battery, characterized in that: The negative electrode active material is one or two of graphite, silicon, lithium titanate and titanium oxide.